2016
DOI: 10.1177/1076029615572467
|View full text |Cite
|
Sign up to set email alerts
|

Serum Apelin 13 Levels in Patients With Pulmonary Embolism

Abstract: This study demonstrated that apelin 13 levels are elevated in patients with PE. These results suggest that apelin may be a novel biomarker and a potential therapeutic target in patients with acute PE in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…Sensitivity was 92.7% and specificity was 96.7% (95% confidence interval: 0.939 to 0.995, area under ROC curve: 0.979, p<0.001) ( Figure 2). Recently, Sen et al found that serum apelin-13 level was significantly higher in the PTE group than in the control group (p<001) [24]. This result is similar to our study results.…”
Section: Discussionsupporting
confidence: 92%
“…Sensitivity was 92.7% and specificity was 96.7% (95% confidence interval: 0.939 to 0.995, area under ROC curve: 0.979, p<0.001) ( Figure 2). Recently, Sen et al found that serum apelin-13 level was significantly higher in the PTE group than in the control group (p<001) [24]. This result is similar to our study results.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were concurrent with previous studies. [ 28–30 ] On the other hand, our study showed that the administration of PD markedly alleviated lung histopathological alterations, fiber formation, collagen deposition, and decreased elevated α‐SMA levels in MTX‐treated rats. As previously reported, [ 31 ] the current results confirmed the effect PD on reducing hydroxyproline.…”
Section: Discussionmentioning
confidence: 71%
“…However, further studies are required to test these hypotheses. Moreover, higher concentration of apelin (1-13) during severe pulmonary embolism [212], a common complication in COVID-19 and the major cause of death in the patients [213,214], might be suggested as a possible biomarker for diagnosis of the stages of the COVID-19 severity. Losses of taste and smell have also been listed as COVID-19 symptoms which might be due to accumulation of the dynorphin A (1-13).…”
Section: Discussionmentioning
confidence: 99%